Penerapan Dan Implementasi Algoritma Kriptografi Loki97 Dalam Mengamankan File PDF - Pardede, Mikain (STMIK Budi Darma, 2018)
This Loki97 algorithm is an algorithm that has been recognized as an algorithm that can secure data so that the data we store in the form of pdf files cannot be opened carelessly by irresponsible parties. By applying Loki97 algorithm data that is confidential and very important data can be stored safely, many have used the Loki97 algorithm for data security such as in the journal Loki97 cryptographic algorithm implementation on video documents.